128. Association of PBP4 Variants and β-lactam Susceptibility in Enterococcus faecalis. (15th December 2022) - Tran, Truc Cecilia; Simar, Shelby R; Egge, Stephanie L; Atterstrom, Rachel; Dinh, An; Hanson, Blake M; Contreras, German; Zervos, Marcus; Abbo, Lilian M; Shimose, Luis; Shelburne, Samuel A; Arias, Cesar A; et al.
Abstract: Background: Penicillin-binding protein 4 (PBP4) is a low affinity PBP that has been associated with decreased susceptibility to penicillins in Enterococcus faecalis (Efs). In vitro data have shown that changes in the promoter region leading to increased pbp4 gene expression and amino acid changes resulting in active site remodeling contribute to this phenotype. There is limited data on the prevalence of these strains in the United States. We investigated β-lactam susceptibility trends in association with variations in PBP4 (allotypes) and the upstream promoter region. Methods: Efs bloodstream isolates (n=184) were selected from the multicenter VENOUS cohort from 2016 to 2021. Whole genome sequencing (WGS) was performed on all isolates, and changes in the pbp4 gene and promoter region 200 bp upstream of the start codon were identified using Efs JH2-2 as reference. Broth microdilution (BMD) testing for ampicillin (AMP), penicillin (PCN), piperacillin (PIP), and imipenem (IMI) was performed for 81 isolates. Analysis of MICs vs. WGS results was performed. Results: A total of 31 PBP4 allotypes and 10 promoter variations were identified. ST6 isolates most frequently carried the promoter mutation ΔA117 (P6), previously shown to increase expression of the pbp4 gene, with allotype 1 PBP4 (Fig 1 ). ST179 isolates most frequently carried the JH2-2 wild type promoter (P1) with the allotype 30 PBP4. All isolates were susceptible to AMP (MIC50 ≤1 µg/mL, MIC90 2 µg/mL) and PCN (MIC50 ≤2 µg/mL, MIC90 4 µg/mL; Table 1 ). PIP was the least potent β-lactam, with an MIC50 4 µg/mL and an MIC90 of 8 µg/mL. Isolates with the P6 promoter had significantly higher piperacillin MICs (p< 0.0001) as compared to P1. Figure 1. Phylogenetic Tree of E. faecalis Strains Conclusion: Changes in the pbp4 gene promoter correlated with an increase in PIP MICs. Caution should be used when choosing β-lactams other than AMP for definitive treatment deep-seated Efs infections. Disclosures: Cesar A. Arias, MD, PhD, Entasis Phramceuticals: Grant/Research Support|MeMed Diagnostics: Grant/Research Support|Merck: Grant/Research Support William R. Miller, MD, Entasis Therapeutics: Grant/Research Support|UpToDate: Royalties - Topic Contributor.